2013
DOI: 10.1002/2013ja019099
|View full text |Cite
|
Sign up to set email alerts
|

Two‐component model of topside ionosphere electron density profiles retrieved from Global Navigation Satellite Systems radio occultations

Abstract: [1] A simple model for the topside ionosphere region is introduced and applied to fit radio-occultation-retrieved electron density profiles for altitudes above the F2 peak. The model considers two isothermal components representing the population of the O + (ionosphere component) and the H + (protonosphere component) ions. The purpose of the model is to achieve an accurate fit of the observed profiles in the topside ionosphere region while, at the same time, allowing a direct and simple derivation of two impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…More often than not, above the maximum, the data is more linearly correlated with height than below. Therefore, we focused the analysis on the heights above h m and below the transition height to the plasmasphere [see, e.g., González‐Casado et al , ], which is the ionospheric region where the single Chapman layer hypothesis is more realistic.…”
Section: Methodsmentioning
confidence: 99%
“…More often than not, above the maximum, the data is more linearly correlated with height than below. Therefore, we focused the analysis on the heights above h m and below the transition height to the plasmasphere [see, e.g., González‐Casado et al , ], which is the ionospheric region where the single Chapman layer hypothesis is more realistic.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the methodology applied in this study can be found in [3] and [4], we only summarize here the details required to understand how the ionospheric and plasmaspheric electron contents are calculated and the data required to implement the method. First, the improved Abel transform inversion ( [3], [6]) is used to retrieve electron density profiles from a data sample of RO measurements taken by the CF3 constellation.…”
Section: Data Sample and Methodsmentioning
confidence: 99%
“…After the bottom-side plasmaspheric electron density was separated, the remaining electron density profile was integrated to obtain the ionospheric electron content, EC ion . Finally, after having calculated EC ion , the plasmaspheric electron content, EC pl , is calculated as the difference [4]:…”
Section: Data Sample and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, according to González‐Casado et al (), the EDP retrievals from ROs depend only on the electron content (EC) below the LEO so that the EC above the LEO only affects the N e retrievals at the altitudes near the LEO height. However, this finding implies that the TEC‐aided inversion could be affected by some mismodeling because TEC is used instead of EC below the LEO satellite height to describe the horizontal gradient in the electron density around the tangent points of the RO.…”
Section: Introductionmentioning
confidence: 99%